Ion-acoustic Gardner Solitons in electron-positron-ion plasma with two-electron temperature distributions - Rehman, Momin A.; Mishra, M.K. (My University, 2016)
(Received 4 September 2015; accepted 30 December 2015; published online 20 January 2016) The ion–acoustic solitons in collisionless plasma consisting of warm adiabatic ions, isothermal positrons, and two temperature distribution of electrons have been studied. Using reductive perturbation method, Korteweg-de Vries (K-dV), the modified K-dV (m-KdV), and Gardner equations are derived for the system. The soliton solution of the Gardner equation is discussed in detail. It is found that for a given set of parameter values, there exists a critical value of b ¼ Tc=Th; (ratio of cold to hot electron temperature) below which only rarefactive KdV solitons exist and above it compressive KdV solitons exist. At the critical value of b, both compressive and rarefactive m-KdV solitons co-exist. We have also investigated the soliton in the parametric regime where the KdV equation is not valid to study soliton solution. In this region, it is found that below the critical concentration the system supports rarefactive Gardner solitons and above it compressive Gardner solitons are found. The effects of temperature ratio of two-electron species, cold electron concentration, positron concentration on the characteristics of solitons are also discussed.
Keywords: Solitons; Positrons; Ion–acoustic solitons; Adiabatic ions; Isothermal positrons